The PTI to ETI Continuum in Phytophthora-Plant Interactions - Naveed, Zunaira Afzal; Wei, Xiangying; Chen, Jianjun; Mubeen, Hira; Ali, Gul Shad (Frontiers in Plant Science, 2020)
Phytophthora species are notorious pathogens of several economically important crop plants. Several elicitors from Phytophthora spp. have been identified that are recognized by the plant receptors to trigger induced defense responses. Adapted Phytophthora pathogens have evolved multiple strategies to evade host defense. They can either modify or suppress their elicitors to bypass the recognition or modulate the defense responses in multiple ways by deploying hundreds of effectors. Phytophthora spp. effectors have been found to suppress multiple aspects of host defense by interfering with diverse physiological processes through the simultaneous intervention of calcium, MAPK, and phytohormones signaling pathways. In the case of incompatible interactions these modulations are perceived by the plants through resistance genes that lead to activation of downstream components of defense to prevent the spread of the pathogen. These multiple phases of plant-Phytophthora interactions can be summarized well along the lines of PTI-ETS-ETI paradigm but it’s hard to maintain the strict PAMP/effector, PRRs/R genes and ultimately PTI-ETI designations as initially proposed in the zigzag model of plant immunity.